P0125ELECTRON MICROSCOPIC DESCRIPTION OF A SENSITIVE DIAGNOSTIC PROXIMAL EPITHELIAL LYSOSOMAL LESION IN PATIENTS WITH CINAC/CKDU/MEN AND CNI NEPHROTOXICITY. (6th June 2020) - Vervaet, Benjamin; Nast, Cynthia; Jayasumana, Channa; Schreurs, Gerd; Roels, Frank; Herath, Chula; Kojc, Nika; Samaee, Vahid; Rodrigo, Sonali; Gowrishankar, Swarnalata; Mousson, Christiane; Dassanayake, Rajeewa; et al.
Abstract: Background and Aims: In CINAC patients from Sri Lanka, we recently observed a sensitive constellation of proximal tubular cell findings including cellular/tubular atrophy, cell fragment shedding and, by electron microscopy (EM), the presence of an increased number of enlarged lysosomes. Here we focused on precisely defining the EM lysosomal phenotype and evaluating its presence in CINAC/MeN/CKDu cases and controls from other countries. Method: Thirthy-two renal biopsies (18 Sri Lanka, 10 El Salvador, 1 India, 3 France) of patients with a diagnosis of CINAC (CKD 1-3A, 3B) were examined by electron microscopy (EM) in comparison to renal biopsies of normal kidneys at implantation, patients with calcineurin inhibitor (CNI) toxicity (n=17), proteinuric nephropathies (n=15), light chain disease (n=4), several cases on nephrotoxic drugs (lomustine, clomiphene, lithium, tenofovir, cisplatinum) and patients with reduced renal function of various causes (n=20). Results: The aberrant lysosomal phenotypes can be defined as enlarged (>1.2µm) and dysmorphic with a light-medium electron-dense matrix containing dispersed dark electron-dense non-membrane bound round to irregular shaped "aggregates". In addition, indicative clusters of 4-6 smaller lysosomes with the same features could be observed. No cristae or other features of mitochondria, autophagic vacuoles, lipofuscin/ceroid droplets, peroxisomes (marginal plate), lysosomal myeloid bodies (aminoglycoside nephropathy) or electron dense laminated lysosomal inclusions (Fabry disease) were observed. Patients with calcineurin inhibitor nephrotoxicity and several cases on nephrotoxic drugs (lomustine, clomiphene, lithium) and a subset of patients with light chain disease, all conditions that can either directly or indirectly be linked to calcineurin inhibition, presented the same lesions. We present an image set demonstrating the phenotypical consistency of the diagnostic lysosomal lesion versus similar features that are non-diagnostic. Conclusion: A rather sensitive constellation of lysosomal lesions in renal proximal tubular cells was detected associated with CINAC/CKDu/MeN and CNI nephrotoxicity in several countries, suggesting a common new pathomechanistic paradigm where CINAC patients are experiencing a tubulotoxic mechanism similar to CNI nephrotoxicity.